2001
DOI: 10.1182/blood.v98.7.2014
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of a dominant-negative H-Ras into human eosinophils attenuates extracellular signal–regulated kinase activation and interleukin-5–mediated cell viability

Abstract: Inhibition of eosinophil apoptosis by exposure to interleukin-5 (IL-5) is associated with the development of tissue eosinophilia and may contribute to the inflammation characteristic of asthma. Analysis of the signaling events associated with this process has been hampered by the inability to efficiently manipulate eosinophils by the introduction of active or inhibitory effector molecules. Evidence is provided, using a dominantnegative N17 H-Ras protein (dn-H-Ras) and MEK inhibitor U0126, that activation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 45 publications
(64 reference statements)
1
55
1
Order By: Relevance
“…7), suggesting that Ras not only is involved in Th2 cytokine production, but also in eosinophil migration induced by Th2 cytokines. Furthermore, Ras-induced ERK activation also is involved in IL-5-induced eosinophil survival (24). The relative contribution of each to the blockade of airway eosinophilic inflammation cannot be determined from this study.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…7), suggesting that Ras not only is involved in Th2 cytokine production, but also in eosinophil migration induced by Th2 cytokines. Furthermore, Ras-induced ERK activation also is involved in IL-5-induced eosinophil survival (24). The relative contribution of each to the blockade of airway eosinophilic inflammation cannot be determined from this study.…”
Section: Discussionmentioning
confidence: 44%
“…The mechanism of these effects is unknown. Decreased eosinophil infiltration may result from one or more of the following: 1) decreased eosinophil adhesion to vascular endothelial cells (23), 2) decreased Th2 cytokine production, or 3) decreased eosinophil survival (24). We recently have demonstrated that the cytosolic group IV-PLA 2 and its upstream activators, ERK and Ras, regulate ␤ 2 -integrindependent adhesion of eosinophils in vitro (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the process by which cPLA 2 is activated to cause integrin-mediated adhesion remains unknown. HRas has been reported to cause attenuation of IL-5-mediated survival of eosinophils in vitro at 16 h (14). H-Ras also has been reported to enhance both ␤ 1 -and ␤ 2 -integrin-mediated adhesion in nondifferentiated cell systems (15,16).…”
mentioning
confidence: 99%